The State of Public Education in Uzbekistan in the 1950s - Nodira Mustafayeva (Researchparks Publishing, 2022)
The article analyses the construction of schools, the difference in the level of educational institutions between urban and rural areas, the issue of women's education, and innovations in the education system in Uzbekistan. It is concluded that the sphere of education as an important part of social life has developed as an instrument of state policy.